The Role of School Libraries in Enhancing the Interest and Initial Reading Abilities of Elementary School Students - Mahendra, Yasinta; Suprapto, Irawan; Apriza, Berta (West Science Interdisciplinary Studies, 2024)
This research delves into the role of school libraries in enhancing the interest and initial reading abilities of elementary school students. Using a literature review method, the study identifies that the school library is not merely a repository of books but a pivotal learning center crucial in shaping children's literacy. Findings indicate that creative programs such as book clubs, storytelling performances, and other literacy activities create an environment that stimulates students' reading interest, while access to diverse reading materials supports the development of initial reading skills. Integrated strategies of the school library with the curriculum and parental involvement also have a positive impact on shaping the literacy of elementary school students. The conclusion of this research underscores the need for increased investment and attention to the role of the school library as an educational agent supporting literacy development at the elementary level.